Characteristic Study of the MCM-41 Modified with Zn by Direct Synthesis - Nur Hasanah; Sutarno Sutarno; Eko Sri Kunarti (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2018)
Modification of MCM-41 with zinc (Zn) by direct synthesis has been attempted. The aims of this research were (i) to show morphology of MCM-41, (ii) to know the optimal ratio of Si/Zn in MCM-41 modification, and (iii) to know crystallinity and pore diameter of MCM-41 and MCM-41 modified by Zn.  Zn metal added to MCM-41 matrix by direct synthesis used zinc nitrate as precursor with ratio Si/Zn variation. Zn added by direct synthesis to get larger diameter without changing the structure of MCM-41. Characterization of material was used XRD, FTIR, TEM, and N2 adsorption. Characterization of MCM-41 with TEM show that material has spherical shape with uniform pore morphology. The result of XRD show that synthesized MCM-41 has good crystallinity with three peaks observed specific to MCM-41. Ratio of Si/Zn optimal to modification MCM-41 is Si/Zn= 100. Modified MCM-41 show decrease in crystallinity and increase pore diameter that is 35.58 Ǻ compared with MCM-41 with pore diameter 31.42 Ǻ.